Adolescent dysmenorrhoea in general practice: tensions and uncertainties - Dixon, Sharon; Taghinejadi, Neda; Duddy, Claire; Holloway, Flora; Vincent, Katy; Ziebland, Sue (Frontiers in Reproductive Health, 2024)
This Perspectives article reflects on findings from our systematic review about adolescent dysmenorrhoea Q, drawing on sociology of diagnosis theory. We consider tensions and uncertainties between presentation with symptoms of dysmenorrhoea and processes of symptom categorisation and diagnosis in adolescents, tracing these through research and clinical guidance, considering possible implications for clinical practice. We argue that challenges in distinguishing between primary and secondary dysmenorrhoea in research translate into challenges in differentiation in clinical practice. We argue that framing this distinction as clear cut and straightforward belies the well-documented challenges in diagnosis of endometriosis, and that not recognising uncertainty and complexity inherent in this task may benefit neither clinicians nor patients.